Evaluation of indigenous missions of India - Joshi Jayaprakash, L. (Madras, India : Church Growth Research Centre, 1987)
On the Christian missionary movement in India.
Includes indexes.
Bibliography: p. 69-70.
Keywords: Missions -- India; Missions, Indic